2019
DOI: 10.3390/su11010270
|View full text |Cite
|
Sign up to set email alerts
|

Such a Shame! A Study on Self-Perception of Household Food Waste

Abstract: Reducing food waste is globally considered as a key challenge in developing sustainable food systems. Although most food waste is generated at the household level, consumers hardly recognize their responsibility, and the factors underpinning their perception of the quantity of food wasted at home are still unclear. This paper aims to fill this gap by analyzing the results of a large-scale survey conducted in Italy. The perceived quantity of household food waste was measured through a Likert scale and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
91
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 43 publications
15
91
2
4
Order By: Relevance
“…Additionally, on average, they represent the segment that most reuses leftovers, confirming that this practice is useful in reducing wasteful behaviour [8,17]. However, given that its potential is not yet fully appreciated by households, due primarily to uncertainty regarding leftover edibility or safety [19,28], it is crucial to provide information on managing leftovers, for example, by holding waste cookery classes as suggested by previous research [7,11]. Blue Cluster consumers are also particularly sensitive to environmental concerns related to food waste, confirming the role of concerns in influencing responsible food behaviour and the intention to reduce food waste [11,12].…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Additionally, on average, they represent the segment that most reuses leftovers, confirming that this practice is useful in reducing wasteful behaviour [8,17]. However, given that its potential is not yet fully appreciated by households, due primarily to uncertainty regarding leftover edibility or safety [19,28], it is crucial to provide information on managing leftovers, for example, by holding waste cookery classes as suggested by previous research [7,11]. Blue Cluster consumers are also particularly sensitive to environmental concerns related to food waste, confirming the role of concerns in influencing responsible food behaviour and the intention to reduce food waste [11,12].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the regions in southern Italy show a lower incidence of food waste than that Sustainability 2020, 12, 1495 9 of 13 in central or northern Italy [30,39]. However, it must be highlighted that previous research showed that the self-assessment of household food waste is systematically underestimated [28,30,39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations